Shifting from Eurocentrism to Afrocentrism : reimagining the curriculum and pedagogy of human rights education at selected law faculties in Commonwealth Africa - Viljoen, Frans (University of Pretoria, 2025)
Thesis (LLD (Multidisciplinary Human Rights))--University of Pretoria, 2025.